Effect of corrugation profile on the thermal-hydraulic performance of corrugated channels using CuO-water nanofluid - Ahmed M.A.; Yusoff M.Z.; Ng K.C.; Shuaib N.H. (Elsevier Ltd, 2023)
In this article, laminar flow and heat transfer characteristics of CuO-water nanofluid in straight and corrugated channels are numerically investigated over the Reynolds number and nanoparticles volume fraction ranges of 100-800 and 0-0.05, respectively. The governing equations in body-fitted coordinates are discretized using finite volume approach (FVM) on a collocated grid and solved iteratively using SIMPLE technique. Three different shapes of corrugated channels such as sinusoidal, triangular and trapezoidal channel are considered in this study. The streamwise velocity contours, temperature contours, non-dimensional pressure drop, average Nusselt number and thermal-hydraulic performance factor are presented and analyzed. Results show that the average Nusselt number and thermal-hydraulic performance factor increases with increasing nanoparticles volume fraction and Reynolds number for all channel shapes. In addition, the non dimensional pressure drop increases with increasing nanoparticles volume fraction, while it decreases as Reynolds number increases for all channel geometries. Furthermore, the trapezoidal channel has the highest Nusselt number and followed by the sinusoidal, triangular and straight channel. © 2014 The Authors. Published by Elsevier Ltd.